2017
DOI: 10.1002/hpm.2464
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of empirical studies on methodology and burden of informal patient payments in health systems

Abstract: There are a number of strategies for the measurement of IPPs with different strengths and weaknesses. Most applied strategies for general public were quantitative surveys recruiting more than 1000 participants using a face-to-face structured interview, and then qualitative studies on less than 150 health care providers, with focus group discussion. This review provides a comprehensive picture of current informal patients' payments measurement tools, which helps researchers in future investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…This is important, as our study confirmed that the prevalence of IPs for inpatient health care services, even after the revision of the medical tariff schedule, is still 14%. These findings correspond to a previously reported range of IPs in the Iranian health care sector of 7-10% in a hospital department to 20-48% in the whole hospital [17], as well as an overall level of IPs in other countries, varying from 2 to 80% [26]. We believe that this relatively low reported prevalence of IPs could be reasonable, given the adjustment of the medical tariffs and the introduction of the new hotline, which allows for real-time feedback by patients who paid IPs and subsequent actions to investigate all cases.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is important, as our study confirmed that the prevalence of IPs for inpatient health care services, even after the revision of the medical tariff schedule, is still 14%. These findings correspond to a previously reported range of IPs in the Iranian health care sector of 7-10% in a hospital department to 20-48% in the whole hospital [17], as well as an overall level of IPs in other countries, varying from 2 to 80% [26]. We believe that this relatively low reported prevalence of IPs could be reasonable, given the adjustment of the medical tariffs and the introduction of the new hotline, which allows for real-time feedback by patients who paid IPs and subsequent actions to investigate all cases.…”
Section: Discussionsupporting
confidence: 91%
“…For future healthcare reforms assessment, we recommend conducting well-planned and timely evaluations, using before and after design, applying similar evaluation methodology, as well as setting up a cohort follow-up, if possible. We found that the prevalence of IPs was higher in private hospitals, like previous studies conducted in Iran and other countries [17,22,26,29,30], confirming that the type of hospital ownership is one of the factors contributing to IPs prevalence. We recommend paying more attention when designing future policy interventions to control IPs in the private sector as well.…”
Section: Actors and Stakeholderssupporting
confidence: 87%
“…Based on the available scientific evidence, one of the most suitable methods for collecting data about the informal payments is the use of a researcher-made questionnaire designed according to the specific features of each country, and completed by face-to-face interviews with the healthcare recipients. 31,32 However, the researchers did not find any standard questionnaire on the factors affecting informal payments in Iran upon literature review. Therefore, a structured questionnaire was prepared and standardized by using the factors extracted from the systematic review of factors that affect informal payments, and by holding a focus group discussion with a panel of 15 related experts who reviewed and examined the questions.…”
Section: Methodsmentioning
confidence: 99%
“…Greater information asymmetry, getting more urgent and critical services in the hospital wards, and higher patient stress for receiving such services can cause patients who use these services to opt for informal payments much more than others. 21,31,46 Also, the results showed that the odds of paying informal payments in services such as dental and emergency services is higher, so that the use of dental and emergency services increased the probability of paying informal payments three and two times, respectively (ORs = 3.02, 2.09; P < 0.001). The higher probability of paying informal payments for dental services can be due to higher patients' out-ofpocket share in dental costs and less insurance coverage for these services in Iran.…”
Section: Factors Affecting Informal Paymentsmentioning
confidence: 98%
“…To our knowledge, an extensive literature is available on IPs prevalence in inpatient services, due to the well-known methodology of measuring IPs and the feasibility of data gathering in inpatient services (19). Based on this evidence, high prevalence of IPs, ranging from 7-10% in a hospital department to 20-48% in the whole hospital is still a major challenge in the Iranian healthcare system for many years (20).…”
Section: Introductionmentioning
confidence: 99%